Arsitektur Islam Vernakular sebagai Wujud Keberlanjutan Sosial dan Spiritual Masyarakat Muslim Lokal - Mohamad Alfian Nur Aziz; Imam Kharomen (CV SCRIPTA INTELEKTUAL MANDIRI, 2025)
Vernacular Islamic architecture represents the connection between Islamic values and local wisdom that developed in the social and cultural context of Muslim communities. This study aims to examine vernacular Islamic architecture as a form of social and spiritual sustainability of local Muslim communities through a conceptual approach. The research method used is non-empirical qualitative with a critical literature review of scientific sources in the form of reputable journals, dissertations, and academic publications relevant to Islamic architecture, vernacularity, and sustainability. The results of the study show that vernacular Islamic architecture not only functions as a space for worship, but also as a medium for collective identity formation, strengthening social relations, and internalizing spiritual values in everyday life. The discussion reveals that sustainability in vernacular Islamic architecture is holistic because it encompasses social, spiritual, cultural, and ecological dimensions that are integrated into community spatial practices. The conclusion of this study affirms that vernacular Islamic architecture has a strategic role in maintaining the continuity of values and the life of local Muslim communities amid the dynamics of social change and modernization..